Pengaruh Kepemilikan Saham oleh Publik dan Corporate Social Responsibilty dengan Variabel Kontrol Struktur Modal dan Aktivitas terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 - 2020 - Novalia; Irham Lihan; Muslimin Muslimin (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
This study aims to determine the effect of public share ownership and corporate social responsibility with capital structure and activity control variables on the profitability of manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020. The variable used to measure profitability is Return On Equity (ROE). The research population is manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique used is purposive sampling, namely sampling using certain criteria. The criteria used are companies in the manufacturing category, before and until the end of the research year are still listed on the Indonesia Stock Exchange (IDX), manufacturing companies that have regular financial reports and have complete financial statements and provide all the data needed regarding research variables. Based on these criteria, the number of samples is 110 manufacturing companies. The test results show that public ownership affects the company's profitability, corporate social responsibility affects the company's profitability, capital structure affects the company's profitability, and activities affect the company's profitability. With an R2 value of 77.6 %.